Tactical Activities to Improve the Effectiveness of Concrete Batching Plant Based on Overall Equipment Effectiveness Analysis - Ekawati, Yurida; Sutrisno, Iddo Christian; Oktiarso, Teguh (Universitas Negeri Malang, 2024)
The growth of infrastructure projects has led to an increased demand for ready-mix concrete. A company that produces ready-mix concrete using a batching plant encountered difficulties in fulfilling customer orders due to the high rate of machine downtime. Overall equipment effectiveness (OEE) was employed to examine these issues at the tactical activities, where the root causes of losses that occur in the OEE components of availability, performance, and quality were addressed. The OEE analysis was extended to encompass maintenance effectiveness measures, as the anticipated solution to the problem was not the replacement of the machine, but rather an enhancement of its operational efficacy. The effectiveness of maintenance activities was measured using MTTF (mean time to failure), MTTR (mean time to repair), and MTBF (mean time between failure). A review of the OEE components revealed a necessity to reduce losses, as evidenced by the availability and performance rates. Although the performance rate has the lowest value, based on the frequent occurrence of failures to the availability component, the improvement process was carried out to overcome problems in the availability variable. The implementation of scheduled maintenance at the beginning of each month and the implementation of daily checks before and after the machine was used resulted in an increase in the OEE value from 56.62% to 71.15%. The incorporation of maintenance analysis into OEE has been shown to result in increased OEE values, as evidenced by a longer mean time between failures, a reduced time for process adjustments, and a decreased asset repair time.